2017
DOI: 10.1002/gps.4796
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of physical activity among depressed older people in six low‐income and middle‐income countries: A community‐based cross‐sectional study

Abstract: The current data provide guidance for future interventions across LMICs to assist older people with depression engage in regular PA. The promotion of social cohesion may increase the efficacy of future public health initiatives, while from a clinical perspective, somatic co-morbidities, MCI, pain, and slow gait need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 71 publications
2
12
1
1
Order By: Relevance
“…It is consistent with the figures calculated by some recent studies concerning the senior population in China (Li et al, 2014;Li et al, 2012), and is significantly higher than that was found two decades ago (3.86%) (Chen et al, 1999). Moreover, it is far beyond the average level of LMICs (Stubbs et al, 2016;Vancampfort et al, 2018) and even some developed countries (Jung et al, 2018;Mc Dowell et al, 2018). This not only warns about the daunting challenge China faces in terms of the increasing burden of depression, but also reminds us the urgent need for more accessible and viable approaches in a context with insufficient professional resources.…”
Section: Prevalence Of Depressionsupporting
confidence: 91%
“…It is consistent with the figures calculated by some recent studies concerning the senior population in China (Li et al, 2014;Li et al, 2012), and is significantly higher than that was found two decades ago (3.86%) (Chen et al, 1999). Moreover, it is far beyond the average level of LMICs (Stubbs et al, 2016;Vancampfort et al, 2018) and even some developed countries (Jung et al, 2018;Mc Dowell et al, 2018). This not only warns about the daunting challenge China faces in terms of the increasing burden of depression, but also reminds us the urgent need for more accessible and viable approaches in a context with insufficient professional resources.…”
Section: Prevalence Of Depressionsupporting
confidence: 91%
“…Future research should explore why unemployment, for example, due to retirement, is an influential factor in the association between physical activity and loneliness in these two countries. At least, it is known that middle‐aged and old‐age people in LMICs who are employed are more physically active . Speculatively, employment may offer opportunities for social connection, enhance social functioning, and, consequently, provide more opportunity to be active, to feel as a meaningful contributor to society, and to feel less lonely …”
Section: Discussionmentioning
confidence: 99%
“…At least, it is known that middle-aged and old-age people in LMICs who are employed are more physically active. 48,49 Speculatively, employment may offer opportunities for social connection, enhance social functioning, and, consequently, provide more opportunity to be active, to feel as a meaningful contributor to society, and to feel less lonely. [50][51][52] Social cohesion was a particularly strong confounder in Russia.…”
Section: General Findingsmentioning
confidence: 99%
“…Disability creates a vicious cycle of poverty through lack of access to education and employment, and through increased out of pocket expenditure (OOP). Even a small OOP expenditure on health can put them at risk of drifting to below poverty line, especially for households that are just above the poverty line (van Doorslaer et al, 2006). Though the life expectancy of the general population has increased due to education, per capita income, living conditions and medical practices (Wang et al, 2017), life expectancy has not increased in the same extent for people with disabilities (Murray et al, 2015).…”
Section: Introductionmentioning
confidence: 99%